PENGARUH CORPORATE GOVERNANCE (KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, KOMISARIS INDEPENDEN, KOMITE AUDIT) DAN KUALITAS AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2013-2015) - Mei Nilasari, 13.05.52.0093; Kartika, Andi (Students Journal of Accounting and Banking, 2017)
This study aimed to analyze the influence of Corporate Governance (Managerial Ownership, Institutional Ownership, Independent Commissioner, Audit Committee) and Quality Audit Integrity Financial Statements Against the Manufacturing Companies Listed on the Stock Exchange Period 2013-2015. The population in this study are all Manufacturing Companies Listed on the Stock Exchange Period 2013-2015. The sample selection using purposive sampling method. The analytical tool used in this research is multiple linear regression analysis. The result shows that the Corporate Governance (Managerial Ownership, Institutional Ownership, Independent Commissioner, Audit Committee) and Quality Audit together influential Against Integrity Financial Statements and the coefficient determinant research partial hypothesis indicates that the Audit Committee significant positive effect against the Integrity Reports Finance. Managerial Ownership, Institutional Ownership and Quality Audit Integrity Against effect does not affect the Financial Statements. While the Independent Commissioner Against significant negative effect Integrity Financial Statements.Keywords: Integrity Financial Statements, Managerial Ownership, Institutional Ownership, Independent Commissioner, Audit Committee and Audit Quality